Project-based biotechnology learning in teacher education to improve pre-service biology teacher higher order thinking skills - Retnita Ernayani Lubis; Alfi Sapitri (Universitas Islam Negeri Sumatera Utara, 2025)
Biotechnology learning in higher education is often theoretical and lacks challenges for students to develop higher-order thinking skills (HOTS). In fact, the ability to analyze, evaluate, and create is crucial for prospective biology educators in the 21st century. This study aimed to enhance students' HOTS through the implementation of project-based learning (PjBL) in biotechnology instruction. The subjects were eight Biology Education students at the Islamic University of North Sumatra (UISU) enrolled in a Biotechnology course. A mixed-methods sequential explanatory design with one-group pretest-posttest was employed. Instruments included HOTS tests in the form of essay questions developed based on the revised Bloom's taxonomy in the cognitive domains C4 (analyze), C5 (evaluate), and C6 (create), as well as observation sheets, logbooks, interviews, and Focus Group Discussion. The results showed a significant increase in HOTS scores (pretest=48.75; posttest=82.50; N-gain=0.66, medium category; Cohen's d effect size=2.86). The highest improvement was observed in the creating indicator (C6, N-gain=0.71). Qualitative analysis revealed five themes of HOTS development processes: facing ambiguity as a trigger for analysis, experimental failure as a means of evaluation, collaboration fostering critical argumentation, project freedom nurturing creativity, and metacognitive reflection. The quality of project products (biofertilizers) was positively correlated with HOTS improvement (r=0.82). It is concluded that project-based biotechnology learning effectively enhances students' HOTS. This model is recommended for implementation in Biotechnology courses within Biology Education study programs.